Meningkatkan Aktivitas, Keterampilan Berpikir Kritis, dan Hasil Belajar Menggunakan Model BATANDING di Sekolah Dasar - Nadia; Raihanah Sari (CV. ITTC INDONESIA, 2023)
Problems in research are low activity, critical thinking skills, and learning outcomes. The aim of the research is to describe teacher activities, analyze student activities, critical thinking skills, and learning outcomes through the use of the BATANDING model. Research using Classroom Action Research was carried out in 4 meetings in class V of SDN Kuin Selatan 1 Banjarmasin in the 2022/2023 academic year with a total of 17 students. Data collection instruments through observation and tests. Qualitative and quantitative data types were analyzed using descriptive techniques in the form of tables, graphs, interpretation in percentages. The results of the research stated that teacher activity obtained a score of 31 for the very good criteria, student activity percentage of 100% all students are very active criteria, critical thinking skills percentage of 88% almost all students are very skilled